(untitled) - Phillips, Roger (Willowdale, Ont., 2002)
Roger Phillips and Martyn Rix are pioneers in the use of photography in plant illustration. The Botanical Garden I and II, are exciting and thoroughly modern renditions of illustrated botany books. Ten years in the making, this set combines the finest in photography with up-to-date, expert commentary to bridge the gap between gardener-friendly books and scientific texts. In the tradition of the great botanical illustrations, each featured plant has been carefully photographed -- as a whole and in its parts -- against a white background to reveal the plant's physical characteristics in exacting detail. Plants from more than 1,200 distinct groups are described -- from oaks to violets and water lilies to grasses -- and are presented in evolutionary order, from the most primitive to the most advanced. Each plant listing includes: - Name: genus, species and common names, date of discovery, and range. - Description: detailed and concise in the scientific style. - Key Recognition Features. - Ecology and Geography. - Comment: cultivation needs plus notes about unusual hybrids or developments in the genus. As a pair, the two volumes are an all-inclusive source of information and photographs of more than 2,000 genera of temperate plants. Thorough introductory text encompasses numerous themes in botany, from the history of plant development to current DNA studies that are revolutionizing plant classification. Each volume includes a detailed index and bibliography. The Botanical Garden I and II are exciting additions to a gardening bookshelf. They are visually rich and highly accurate references that will remain interesting, useful and current for many years. Offering a discerning insight into the relationship between garden plants and their natural environments and accuracy that is unequalled outside scientific circles, this duo are truly the modern heirs to a long history of botanical references. There are simply no other works of this kind available today. About Volume II, Perennials and Annuals The second in the two volumes of The Botanical Garden, this illustrated reference covers 515 genera of herbaceous temperate plants, including annuals, biennials, perennials, bulbs and aquatic plants. All are described in complete detail, including how plants are related and their origins and uses. Previously imprecise classifications are corrected. Listings are organized in evolutionary order, from the ancient plants -- sphagnum moss and ferns -- to the modern irises, hostas and sedges.
Keywords: Plants, Ornamental.,Cây cảnh, trang trí